Rosneft: On the road to global NOC status? - James Henderson (The Oxford Institute for Energy Studies, 2012)
Since the election of Vladimir Putin as president of Russia in 2000 Rosneft has become one of the cornerstones of the strategy for the Russian state to retake control over the `commanding heights' of the economy, and in particular the energy sector. However, having now established itself as a global-scale oil company, Rosneft faces a number of significant challenges. In common with many NOCs, its global significance is based entirely on its domestic asset base, and despite the size of Russia's resources Rosneft does face the problem that its existing assets in the core areas of West Siberia and European Russia are going into gradual decline. This decline can be offset by the development of new areas such as East Siberia, the Arctic, and offshore fields, but these regions are remote and their exploitation will require advanced and expensive new technology. In parallel with this issue Rosneft is also facing pressure from its majority owner, the Russian government, to act as a catalyst for establishing a greater role for Russia in the global economy, using its energy resources as an important tool. The company is therefore looking to increase the diversity of its asset base by investing overseas at a time when the competition for global oil reserves is high and when Rosneft itself has limited experience of dealing in the international asset market. This paper explores how Rosneft may be attempting to meet these twin challenges, using the example of two peer NOCs that have experienced similar problems. Petrobras and Statoil are partially privatized, upstream focused NOCs who have established international businesses both as a way of supplementing and diversifying their domestic resource bases and also as a means of acquiring and exploiting technological and operating experience that could be applied across their asset portfolios. Both companies also have a much longer history as corporate entities than Rosneft, and gained listings on an international stock exchange (in New York) in 2000-2001, five to six years before Rosneft's own privatization. As a result, they can provide a clear analogy for the strategy and tactics that Rosneft may use in the development of its own business model, and indeed it appears that in 2011 Russia's NOC is already taking a similar path to its `Partial NOC' peers.
Keywords: 330; Privatisierung; Unternehmensgeschichte; Mineralölwirtschaft; Russland